Urban versus rural setting as a predictor of injury type and severity among pediatric pedestrians: using a database derived from state-wide crash data and hospital discharge data in Illinois. Issue 1 (24th October 2020) - Fant, Colleen; Koopmans, Joy; Simon, Norma-Jean E.; Lorenz, Doug; Rychlik, Karen; Sheehan, Karen
Abstract: We obtained and linked data from the Illinois Department of Transportation and the Illinois Hospital Discharge Data System 2008 − 2015. We evaluated differences in demographic characteristics, injury severity and type among cases and examined associations among injury type, severity, and crash location. There were 11, 303 injured pedestrians under 19 years of age and 46% matched to hospital data. Demographic characteristics were similar to unlinked cases. Among linked cases, fractures, traumatic brain injury, open wound or amputation, and internal organ injuries occurred more often in rural areas (p < 0.001), as were more severe injuries (p < 0.001). Mild injury and soft tissue injuries occurred more often in urban areas (p < 0.001). These data can inform targeted interventions for injury reduction. Preliminary investigations found that more severe injuries and specific injury types are more likely to occur in rural versus urban settings. Our combined database approach may be extended to other databases.